Differences in Awareness of Pre-exposure Prophylaxis and Post-exposure Prophylaxis Among Groups At-Risk for HIV in New York State: New York City and Long Island, NY, 2011–2013. (1st July 2017) - Walters, Suzan M.; Rivera, Alexis V.; Starbuck, Lila; Reilly, Kathleen H.; Boldon, Nyasha; Anderson, Bridget J.; Braunstein, Sarah
Abstract : Background: Pre-exposure prophylaxis (PrEP) to reduce the risk of HIV was approved in 2012 and post-exposure prophylaxis (PEP) in 2005. We report the differences in awareness of PrEP/PEP and factors associated with awareness by examining 3 risk groups (men who have sex with men (MSM), people who inject drugs, and high-risk heterosexuals). Methods: National HIV Behavioral Surveillance system data collected in New York City (NYC) and Long Island, NY in 2011–2013 were used. Logistic regressions by region were developed to estimate adjusted associations [Adjusted Odds Ratios (AOR)] and determine differences in awareness of PrEP/PEP. Results: Awareness of PrEP/PEP was low for all groups. In multivariate analysis controlling for sociodemographic factors, noninjection drug use, HIV status, and exposure to HIV prevention, males who inject drugs in NYC had significantly decreased odds of PrEP/PEP awareness [AOR: 0.45; confidence interval (CI): 0.25 to 0.81] compared with MSM. MSM aged 18–29 years had increased awareness of PrEP (AOR: 2.94; 95% CI 1.11 to 7.80). On Long Island, females who inject drugs (AOR: 0.18; 95% CI: 0.05 to 0.62), males who inject drugs (AOR: 0.14; 95% CI: 0.05 to 0.39), female heterosexuals (AOR: 0.25; 95% CI: 0.11 to 0.59), and male heterosexuals (AOR: 0.32; 95% CI: 0.14 to 0.73) had significantly decreased odds of PrEP/PEP awareness. Black MSM had increased awareness of PrEP (AOR: 4.08 CI:1.21 to 13.73). Conclusions: Large proportions of groups at-risk for HIV were unaware of PrEP/PEP. When comparing risk groups to MSM, we found MSM to have greater awareness in both regions. On Long Island, people who inject drugs and heterosexuals were far less likely to have PrEP/PEP awareness than in NYC. On Long Island, Black MSM had increased PrEP awareness and in NYC MSM aged 18-29 had increased PrEP awareness. These findings suggest that awareness may be spreading through networks and highlight the importance of targeted educational and prevention efforts by group and region.